REVASCULARISATION STRATEGY IN THE CRITICAL LEFT MAIN CORONARY ARTERY DISEASE ASSOCIATED WITH ACUTE CORONARY SYNDROME AND CHRONIC TOTAL OCCLUSION OF RIGHT CORONARY ARTERY - Maričić, Bojan; Perišić, Zoran; Kostić, Tomislav; Apostolović, Svetlana; Šalinger, Sonja; Božinović, Nenad (Acta medicae Medianae, 2023)
Critical left main stenosis combined with chronic total occlusion of the right coronary artery and cardiogenic shock in acute myocardial infarction has been the most challenging case for an interventional cardiologist. Emergency revascularization, CABG or PCI is mandatory. A 46-year-old man presented with non-ST-elevation myocardial infarction and cardiogenic shock. Coronary angiography revealed chronic total occlusion in the middle portion of RCA and severe bifurcation stenosis of the distal left main (LM). LM bifurcation stenosis includes stenosis of the distal LM 80%, ostial stenosis left anterior descending artery (LAD) 80%, ostial stenosis, left circumflex artery (LCX) 90%. A decision was made to perform a two-step procedure, the first one immediately to solve the lesion of the left main, and the PCI CTO RCA in another act. Considering coronary anatomy, we decided to do the “TAP“ (T and protrusion) technique for LM. RCA recanalisation was performed six months later.
Keywords: left main coronary artery, acute coronary syndrome, surgery, percutaneous intervention, chronic total occlusion